Activation of Bone Marrow Adaptive Immunity in Type 2 Diabetes: Rescue by Co-stimulation Modulator Abatacept - Santopaolo, Marianna; Sullivan, Niall; Thomas, Anita Coral; Alvino, Valeria Vincenza; Nicholson, Lindsay B.; Gu, Yue; Spinetti, Gaia; Kallikourdis, Marinos; Blom, Ashley; Madeddu, Paolo (Frontiers in Immunology, 2021)
Abstract Background: Chronic low-grade inflammation and alterations in innate and adaptive immunity were reported in type 2 diabetes (T2D). Here, we investigated the abundance and activation of T cells in the bone marrow (BM) of patients with T2D. We then verified the human data in a murine model and tested if the activation of T cells can be rescued treating mice with Abatacept, an immunomodulatory drug employed for the treatment of rheumatoid arthritis. Clinical evidence indicated Abatacept can slow the decline in beta-cell function. Methods: A cohort of 24 patients (12 with T2D) undergoing hip replacement surgery was enrolled to the study. Flow-cytometry and cytokine analyses were performed on BM leftovers from surgery. We next compared the immune profile of db/db and control wt/db mice. In an additional study, db/db mice were randomized to receive Abatacept or vehicle for 4 weeks, with endpoints being immune cell profile, indexes of insulin sensitivity, and heart performance. Results: T2D patients showed increased frequencies of BM CD4+ (2.8-fold, p=0.001) and CD8+ T cells (1.8-fold, p=0.01), with upregulation of the activation marker CD69 and homing receptor CCR7 in CD4+ (1.64-fold, p=0.003 and 2.27-fold, p=0.01, respectively) and CD8+ fractions (1.79-fold, p=0.05 and 1.69-fold, p=0.02, respectively). These differences were confirmed in a multivariable regression model. CCL19 (CCR7 receptor ligand) and CXCL10/11 (CXCR3 receptor ligands), implicated in T cell migration and activation, were the most differentially modulated chemokines. Studies in mice confirmed the activation of adaptive immunity in T2D. Abatacept reduced the activation of T cells and levels of pro-inflammatory cytokines, and improved cardiac function, but not insulin sensitivity. Conclusions: Results provide proof-of-concept evidence for the activation of BM adaptive immunity in T2D. In mice, treatment with Abatacept dampens the activation of adaptive immunity and protects from cardiac damage.